Finite Element Analysis of Super Energy Saving Locking System Towards Enhancing Door Lock Performance and Security - Sivarao, Subramonian; Alif, Aziz; RAJA ABDULLAH, RAJA IZAMSHAH; Taufik; Hambali, A (Praise Worthy Prize, 2013)
This paper presents an innovative Super Energy Saving Locking System (SES-Lock) which was derived to overcome the limitations faced by the popularly being used electro magnetic (EM- Lock) door locks. EM-Lock continuously consumes electricity (almost 24 hours) let it to be when the door is in the locked or unlocked conditions, besides requiring a backup battery in case of power failure to avoid the lock from malfunction. It is also pretty much easier to be electrically or mechanically hacked with a little bit of skill in breaking in. Therefore, Super Energy Saving Locking System (SES-Lock) was critically engineered, in such a way that it does not at all consume power supply when the door is in the locked or unlocked conditions, which enabled the power saving almost up to 95% compared to EM lock of the same capacity. The system was also intelligently innovated in which no back-up battery is required for SES-Lock during a power failure, where the system can still remain locked as usual and can be easily opened using embedded fail safe and fail secure administrative key operated mechanically. SES Lock is fully compatible and can be integrated with the common door access control system regardless of its type namely key pad, card swipe, or biometric. Its body structure was designed with Al alloy 6061-T6 material to withstand if not same for better mechanical and electrical performance compared to EM-Lock.